Rich dad, poor dad : what the rich teach their kids about money--that the poor and middle class do not! - Kiyosaki, Robert T., 1947- (Scottsdale, AZ : Plata Pub., 2017)
Robert T. Kiyosaki offers non-traditional financial advice and investment strategies based on the monetary lessons he learned from his two fathers of varying financial success.
Subtitle from the front cover.
"With updates for today's world--and 9 new study session sections."
Adult
Adult
860L
Keywords: Finance, Personal; Investments; Rich people; Personal finance; Investments; Rich